Attachment and self-regulation in the workplace—a theoretical integration - Ren, Queyu; Topakas, Anna; Patterson, Malcolm (Frontiers in Psychology, 2024)
Interest in adopting attachment theory to interpret workplace dynamics is growing, reflected in increasing theoretical development and empirical research. However, the advancement of the field has been hindered by the limited attention paid to the cognitive, affective and behavioral processes involved in carrying the effect of attachment styles on outcomes. Adopting a selfregulatory lens, this paper aims to unpack the attachment black box by integrating attachment theory and self-regulation theory. We propose a theoretical framework that explicates how attachment styles function to shape individuals' regulatory responses from cognitive, affective, and behavioral perspectives, as well as identifying boundary conditions of the activation processes of attachment styles in the workplace. The framework provides novel insights into the effects, mechanisms, and boundary conditions of employee attachment styles in the workplace. Implications of the framework and future research directions are discussed.